Effect of Foreign Direct Investment on Economic Growth in Nigeria and Ghana - Ogbaragu, Justice Sunday; Offor, Nkechi; Orjinta, Ifeoma Hope; Udoezika, David (PT. Riset Press International, 2024)
This quantitative study investigated the effect of Foreign Direct Investment (FDI) on Economic Growth in Nigeria and Ghana using data spanning from 1981 to 2022 sourced from reputable institutions, including the Central Bank of Nigeria, Bank of Ghana, World Bank, International Monetary Fund (IMF), and United Nations Conference on Trade and Development (UNCTAD). Gross Domestic Product (GDP) per capita served as the key indicator of economic growth, calculated by dividing total GDP by population size. FDI, Inflation Rates, and Exchange Rates were examined as independent variables. Ordinary Least Square (OLS) regression analysis was employed, and the model was adapted from previous studies. Descriptive statistics highlighted substantial FDI inflows in both countries, with Nigeria exhibiting a mean FDI of USD 2.47 billion and Ghana's USD 1.13 billion. Analysis revealed the significance of FDI in driving economic growth in both nations, with coefficients of 9.10E-08 for Nigeria and 2.85E-07 for Ghana. Additionally, Exchange Rates demonstrated a positive effect on GDP per capita in both countries, emphasizing the importance of currency stability. Cointegration tests suggested stable long-term relationships between FDI and Economic Growth. The study suggests that both countries should continue implementing policies that attract and retain FDI as clear and stable regulations and incentives for foreign investors can contribute to sustained economic growth.